Efecto de metabolitos y esporas del hongo sarocladium oryzae sawada sobre algunas poaceas - Cruz Triana, A.=700 1 Martinez Coca, B.; Rivero Gonzalez, D.
(Es, En)
Ilus., 8 ref.
Keywords: SAROCLADIUM; POACEAS; METABOLITOS; ESPORAS; CUBA; SAROCLADIUM ORYZAE